2022
DOI: 10.1039/d1qo01935j
|View full text |Cite
|
Sign up to set email alerts
|

Rh(iii)-Catalysed cascade C–H imidization/cyclization ofN-methoxybenzamides with isoxazolones for the assembly of dihydroquinazolin-4(1H)-one derivatives

Abstract: By virtue of isoxazolones as viable imidizating reagents, an efficient Rh(III)-catalysed redox-neutral C-H imidization/cyclization cascade has been developed for the specific assembly of dihydroquinazolin-4(1H)-ones with the equipment of a quaternary...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…For the specific assembly of dihydroquinazolin-4(1 H )-ones that are equipped with a quaternary carbon center, an effective Rh( iii )-catalysed external oxidant-free C–H imidization/cyclization cascade with isoxazolones as viable imidizing reagents has been developed (Scheme 37). 55 With good compatibility and practicality, this approach allows for the simultaneous production of two new C–N bonds in a one-pot fashion. The research identified a tandem sequence for this transformation that includes C–H activation, oxidation addition, C–H amination, isomerization, and intramolecular cyclization, in which the Rh( v ) nitrenoid and imine species may serve as active intermediates.…”
Section: Directing Group Strategies In Rhodium-catalyzed C–h Aminationmentioning
confidence: 99%
“…For the specific assembly of dihydroquinazolin-4(1 H )-ones that are equipped with a quaternary carbon center, an effective Rh( iii )-catalysed external oxidant-free C–H imidization/cyclization cascade with isoxazolones as viable imidizing reagents has been developed (Scheme 37). 55 With good compatibility and practicality, this approach allows for the simultaneous production of two new C–N bonds in a one-pot fashion. The research identified a tandem sequence for this transformation that includes C–H activation, oxidation addition, C–H amination, isomerization, and intramolecular cyclization, in which the Rh( v ) nitrenoid and imine species may serve as active intermediates.…”
Section: Directing Group Strategies In Rhodium-catalyzed C–h Aminationmentioning
confidence: 99%